Novel composite materials consisting of polypyrrole and metal organic frameworks for supercapacitor applications - Kalyon, Hilal Yildirim; Gencten, Metin; Gorduk, Semih; Sahin, Yucel (ELSEVIER, 2022)
In this work, copper and zinc including metal organic frameworks (MOFs) have been synthesized and used as additives in polypyrrole based electronically conducting polymers (ECPs) as electrode materials of super capacitors for the first time in the literature. Prepared powders of metal organic frameworks are characterized by using of spectroscopic methods and thermal methods. Then, the powders are used as additives in-situ electrochemical polymerization of polypyyrole to produce the electrode materials of supercapacitors. In this concept, the important parameters such as sulfuric acid concentration, monomer concentration, cyclic number, and amount of metal organic frameworks in the cyclic voltammetric preparation of conducting polymers have been optimized by using of electrochemical methods. Spectroscopic and microscopic methods are used to characterize the prepared electrodes under optimum conditions. To determine the areal capacitance of the prepared electrodes, cyclic charge/discharge tests have been carried out. Areal capacitances of the electrodes are determined as 234.4 mF.cm(-2) and 127.1 mF.cm(-2) at 1 mA.cm(-2) charge/discharge current densities for MOF-Zn@PA/PPy/ PGE and MOF-Cu@PA/PPy/PGE, respectively.
Keywords: Conducting polymers; Metal organic frameworks; Polypyyrole; Cyclic voltammetry; Galvanostatic charge; discharge; Energy & Fuels